2022
DOI: 10.1002/solr.202200355
|View full text |Cite
|
Sign up to set email alerts
|

Above 23% Efficiency by Binary Surface Passivation of Perovskite Solar Cells Using Guanidinium and Octylammonium Spacer Cations

Abstract: One of the important factors in the performance of perovskite solar cells (PSCs) is effective defect passivation. Dimensional engineering technique is a promising method to efficiently passivate non‐radiative recombination pathways in the bulk and surface of PSCs. Herein, a passivation approach for the perovskite/hole transport layer interface is presented, using a mixture of guanidinium and n‐octylammonium cations introduced via GuaBr and n‐OABr. The dual‐cation passivation layer can provide an open‐circuit v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 89 publications
(126 reference statements)
0
20
1
Order By: Relevance
“…Several theoretical studies, including our own, have shown that altering the distribution of ionic charge, and concurrently the distribution of electrons and holes, can influence rates of non-radiative recombination, which ultimately explains many manifestations of hysteresis in PSCs. 13,15,20,21 In our theoretical exploration of the TCO's influence, we observed that the greater the influence of the TCO on the perovskite layer, the higher the rate of nonradiative recombination at any given defect density due to increased accumulation of minority charge carriers at the TL–TCO interface. This was consistent with our experimental observations in the substitution between TiO 2 and TiO x N y , 1 which showed an ∼8 mV increase in open circuit voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical studies, including our own, have shown that altering the distribution of ionic charge, and concurrently the distribution of electrons and holes, can influence rates of non-radiative recombination, which ultimately explains many manifestations of hysteresis in PSCs. 13,15,20,21 In our theoretical exploration of the TCO's influence, we observed that the greater the influence of the TCO on the perovskite layer, the higher the rate of nonradiative recombination at any given defect density due to increased accumulation of minority charge carriers at the TL–TCO interface. This was consistent with our experimental observations in the substitution between TiO 2 and TiO x N y , 1 which showed an ∼8 mV increase in open circuit voltage.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The surface engineering strategies often include physical or chemical methods of passivation with their distinct benefits including separation of defects from minority charge carriers and reduction of defect states in the perovskite films, respectively. [17] Snaith et al introduced a Lewis base passivation concept for perovskite layer by using the thiophene, pyridine, and iodopentafluorobenzene through supramolecular halogen bonding that effectively reduced the nonradiative recombination. [18] Similarly, the use of long-chain hydrophobic organic molecules resulted in improved performance and stability of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Surface passivation refers to introducing a passivator on the surface of perovskite films to interact with defects through electrostatic or chemical action, and so the carrier recombination caused by defects is suppressed. A considerable number of passivators have been developed to passivate the surface defects of perovskite films, for example, halide salts, polymers, , organic small molecules, ionic liquids, fullerene derivatives, , and low-dimensional perovskites. Organic small molecules have the advantages of good solubility and tunable structures for passivating different kinds of defects and can adapt to a variety of perovskite compositions, which has garnered extensive attention. Choi et al developed an indacenodithieno [3,2-b] thiophene-based small molecule (IDTT-ThCz) to perform surface passivation of perovskite layers.…”
Section: Introductionmentioning
confidence: 99%